The pronociceptive role of 5-HT6 receptors in ventrolateral orbital cortex in a rat formalin test model. (December 2019) - Zhang, Yu-Xiang; Yang, Mei; Liang, Feng; Li, Shao-Qing; Yang, Jing-Si; Huo, Fu-Quan; Yan, Chun-Xia
Abstract: Recent studies have shown the 5-HT6 receptors are expressed in regions which are important in pain processing such as the cortex, amygdala, thalamus, PAG, spinal cord and dorsal root ganglia (DRG), suggesting a putative role of 5-HT6 receptors in pain modulation. The ventrolateral orbital cortex (VLO) is part of an endogenous analgesic system, consisting of the spinal cord – thalamic nucleus submedius (Sm) – VLO – periaqueductal gray (PAG) – spinal cord loop. The present study assessed the possible role of 5-HT6 receptors in the VLO in formalin-induced inflammatory pain model. Firstly we found that microinjection of selective 5-HT6 receptor agonists EMD-386088 (5 μg in 0.5 μl) and WAY-208466 (8 μg in 0.5 μl) both augmented 5% formalin-induced nociceptive behavior. Microinjection of selective 5-HT6 receptor antagonist SB-258585 (1, 2 and 4 μg in 0.5 μl) significantly reduced formalin-induced flinching. Besides, the pronociceptive effects of EMD-386088 and WAY-208466 were dramatically reduced by SB-258585, implicating 5-HT6 receptor mechanisms in mediating these responses. In addition, the pronociceptive effect of EMD-386088 was also prevented by the adenylate cyclase (AC) inhibitor SQ-22536 (2 nmol in 0.5 μl) and the protein kinase A (PKA) inhibitor H89 (10 nmol in 0.5 μl), respectively. We further confirmed the above results with quantification of spinal c-fos expression. Taken together, our results suggested that 5-HT6 receptors play a pronociceptive role in the VLO in the rat formalin test due to its activation of AC - PKA pathway. Therefore, cerebral cortical 5-HT6 receptors could be a new target to develop analgesic drugs. Highlights: Intro-VLO of 5-HT6 receptor agonists enhanced nociceptive behavior and spinal Fos expression. Intro-VLO of 5-HT6 receptor antagonist depressed nociceptive behavior and spinal Fos expression. The pronociceptive effect of 5-HT6 receptor agonists was blocked by 5-HT6 receptor antagonist. The pronociceptive effect of 5-HT6 receptor agonist was blocked by AC inhibitor. The pronociceptive effect of 5-HT6 receptor agonist was blocked by PKA inhibitor.